Rola sądownictwa administracyjnego na przykładzie względnej dewolutywności skargi kasacyjnej wniesionej do Naczelnego Sądu Administracyjnego - Rozczyński, Beniamin; Mączyński, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The important role of administrative courts is to examine the legality of public administration operations, which is a manifestation of the implementation of one of the fundamental constitutional principles, i.e. the principle of a democratic state governed by the rule of law, which gives effect to the principle of social justice. The administrative courts were provided with a new procedural instrument — the exchangeability of a cassation appeal. This institution entitles the voivodship administrative court, which states that in a case the proceedings are invalid or the grounds for the cassation complaint are clearly justified, to revoke the appealed judgment or the decision, also deciding on the application of a party on the reimbursement of the cassation proceedings costs and at the same meeting to reconsider the case.
Keywords: self-control of the cassation appeal; administrative court proceedings; administrative court system